Entanglement at the soft-hair horizon - Sayid Mondal; Wen-Yu Wen (Physics Letters B, 2022)
We study entanglement between two modes of a free bosonic and fermionic field as seen by two relatively accelerating observers at the soft-hair horizon of a four-dimensional supertranslated Schwarzschild black hole. First, we associate the shock wave to the near horizon geometry by explicit construction of map between their metric as well as relation between wave form factor and soft hair function. We then compute mutual information and entanglement negativity as a measure of entanglement between these two observers and show that their angular dependence at the soft-hair horizon. We also show that for vanishing soft hair function our results are equal to that of an ordinary Schwarzschild black hole case.